2017
DOI: 10.1016/j.trsl.2016.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Insulin resistance in Alzheimer's disease

Abstract: The links between systemic insulin resistance (IR), brain-specific IR and Alzheimer’s disease (AD) has been an extremely productive area of current research. This review will cover the fundamentals and pathways leading to IR; its connection to AD via cellular mechanisms, the most prominent methods and models used to examine it, an introduction to the role of extracellular vesicles (EVs) as a source of biomarkers for IR and AD, and an overview of modern clinical studies on the subject. To provide additional con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 101 publications
(91 citation statements)
references
References 236 publications
(210 reference statements)
1
87
0
1
Order By: Relevance
“…From the standpoint of disease pathophysiology, the higher levels seen in AD participants also match the glucose elevation observed in diabetes mellitus,42 potentially due to their common underpinning of brain insulin resistance 43. Besides these earlier MRS findings, a recent human postmortem study also showed a dramatic glucose elevation in all brain regions of the AD specimens examined 44.…”
Section: Discussionmentioning
confidence: 58%
“…From the standpoint of disease pathophysiology, the higher levels seen in AD participants also match the glucose elevation observed in diabetes mellitus,42 potentially due to their common underpinning of brain insulin resistance 43. Besides these earlier MRS findings, a recent human postmortem study also showed a dramatic glucose elevation in all brain regions of the AD specimens examined 44.…”
Section: Discussionmentioning
confidence: 58%
“…Eventually, this signaling culminates in the translocation of insulin-dependent glucose transporter 4 (GLUT4) towards the plasma membrane so that the glucose uptake and energy production could be enhanced. Liver, skeletal muscle and adipose tissue are main targets of insulin action [134, 135]. …”
Section: Major Cancer-related Signaling Pathways With Links To Ad mentioning
confidence: 99%
“…Normally, the activation of the insulin pathway strengthens the degrading process of excessive Aβ and thus effectively avoids the formation of extracellular Aβ plaques. However, when insulin insensitivity occurs in neuronal cells, the functionality of γ-secretase could also be stimulated, which promotes the cleavage of APP into Aβ [142, 143]. Additionally, due to the secondary hyperinsulinemia by insulin non-responsiveness, the expression of insulin-degrading enzyme (IDE) is greatly suppressed, which physiologically functions as a potent scavenger of Aβ in brain cells [144].…”
Section: Major Cancer-related Signaling Pathways With Links To Ad mentioning
confidence: 99%
See 2 more Smart Citations